CURRENT STATUS OF TREATMENT ADHERENCE AND RELATED FACTORS AMONG OUTPATIENTS WITH CHRONIC DISEASES IN THU DUC CITY 2024-2025 - Khoa Lý, Nguyễn; Thị Bích Uyên, Nguyễn; Thị Vân Anh, Trương; Thanh Hương, Lâm; Thị Liên, Phạm (Journal of Health and Aging, 2026)
To describe the current status of treatment adherence among outpatients with chronic diseases and to analyze factors associated with treatment adherence in Thu Duc City during 2024–2025. Cross-sectional descriptive study. The study included 253 patients with hypertension, 150 patients with diabetes mellitus, and 130 patients with chronic obstructive pulmonary disease (COPD) treated at Le Van Viet Hospital and Thu Duc City Medical Center (Facilities 1, 2, and 3) from July 2024 to March 2025. The mean age was 65.7 ± 10.9 years; 52.2% were male and 47.8% were female. The duration of illness was 6.8 ± 6.5 years. Hypertension and diabetes were mostly discovered incidentally; 74.6% of COPD patients were diagnosed when symptoms appeared. 10% of hypertensive patients, 17.3% of diabetic patients, and 6.2% of COPD patients had at least one comorbidity. 67.7% of hypertensive patients had blood pressure <140/90 mmHg. Blood glucose levels were 137.7 ± 50.4 mg/dL (96%). 24.6% of COPD patients were in GOLD stage 3 or 4. The overall treatment adherence rate was 23.8% good, 48.6% fair, and 27.6% poor. Better treatment adherence was observed among patients who lived with family, were diagnosed through regular check-ups, had a disease duration of less than 5 years, and had no comorbidities (p < 0.05). Treatment adherence was significantly associated with achieving treatment goals, particularly among patients with hypertension, and to a lesser extent among those with COPD and diabetes. Conclusion: Treatment adherence plays an essential role in the management of chronic diseases.